2002
DOI: 10.14411/fp.2002.008
|View full text |Cite
|
Sign up to set email alerts
|

Development and release of a malacosporean (Myxozoa) from Plumatella repens (Bryozoa: Phylactolaemata)

Abstract: Abstract. During an experiment to transmit Tetracapsula bryosalmonae Canning, Curry, Feist, Longshaw et Okamura, 1999 to a laboratory-cultured bryozoan, Plumatella repens L. a previously undescribed malacosporean species was noted. This parasite produced sacs of spores in the host that reached 1.2 mm in length. The spores released from the sacs appeared similar in size to the two species of Tetracapsula previously described although slight differences in form were noted. Release of spores from the bryozoans wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 20 publications
5
35
0
Order By: Relevance
“…During capsulogenesis, external tube of the capsular primordium is not always observed but has been proven in some populations. In some malacosporean populations spores arise in the layer of mural cells (Morris et al 2002).…”
Section: Class Malacosporea Canning Curry Feist Longshaw Et Okamurmentioning
confidence: 99%
“…During capsulogenesis, external tube of the capsular primordium is not always observed but has been proven in some populations. In some malacosporean populations spores arise in the layer of mural cells (Morris et al 2002).…”
Section: Class Malacosporea Canning Curry Feist Longshaw Et Okamurmentioning
confidence: 99%
“…Only minimal morphological differences have been recorded between spores of different malacosporean species. Morris et al (2002) documented ornamented spores with a mean diameter of 19.0 µm in the bryozoan Plumatella repens infected with worm-like malacosporean stages. The spores observed by McGurk et al (2006a), also released by a worm-shaped malacosporean in P. repens, were spherical and 17.7 µm in diameter.…”
Section: Morphology Of Malacosporeans In Bryozoan Hosts (Bryozoa-spores)mentioning
confidence: 99%
“…D. C. Morris et al (2002a) and D. J. Morris et al (2002) reported possible transmission of T. bryosalmonae and Buddenbrockia plumatellae from fish to bryozoans. However, these results may have reflected previous development of infection in bryozoans in the field, or PCR amplification of residual DNA that had adhered to bryozoans or of DNA from undetected, infected invertebrates.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Morris et al 2002). However, even if such transmission is eventually demonstrated, it may only be facultative since infected bryozoans occur in sites lacking salmonids in Ohio and Michigan .…”
Section: Constraints Of Studymentioning
confidence: 99%